On the edge : women's experiences of Queensland - Reekie, Gail (Studies in Australian history (St. Lucia, Qld.), 1994)
On the Edge: Women's Experiences of Queensland is the first-ever specific study of Queensland women. It brings together the work of several of the state's foremost feminist scholars, who use a number of perspectives - historical, literary, cultural and political - to explore the distinctive experiences of women in Queensland. Subjects covered include the sexual economics of colonial marriage, the YWCA travelling caravan and women's war mobilisation. Contemporary issues affecting Queensland women such as sexual harassment legislation and rape crisis service provision are also discussed. On the Edge investigates the important question of how best to bring together feminism and regionalism, and restores to the women of Queensland their history.